A mechanical impedance approach for structural identification, health monitoring and non-destructive evaluation using piezo-impedance transducers - Suresh Bhalla. (2008)
This research has focused on utilizing the underlying PZT-structure electro-mechanical interaction for an impedance based structural identification and SHM/ NDE using the EMI technique. A new concept of active signatures has been introduced to extract the damage-sensitive information from the raw signatures and a new PZT-structure interaction model has been developed based on the concept of 'effective impedance'.A new experimental technique has been developed to 'update' the model of the PZT patch.A unified impedance approach has been developed to 'identify' the host structure from the extracted mechanical impedance spectra and carry out quantitative and parametric damage prediction.